Factors Influencing University Sustainability Reporting - Raharja, Surya; Maylia Pramono , Sari (Accounting Analysis Journal, 2024)
Purpose : The research analyses the factors that influence university Sustainability Reporting (SR) practices consisting of external assurance, internal auditor, signed declaration, sustainability office and stakeholder engagement. Method : The research uses descriptive, content analysis, and multivariate regression analysis were employed to analyse the data and test the hypotheses. Observational data from 155 universities registered in the Global Reporting Index (GRI) Database from 2010 to 2020 was analysed to examine the relationship between university sustainability reporting with external assurance, internal auditors, signed declaration, sustainability offices and stakeholder involvement with sustainability reporting. Findings : The findings indicate that external assurance, internal auditors, signed declaration, sustainability offices positively influence sustainability reporting. Stakeholder engagement has no influence sustainability reporting. These results underline the impact of factors that influence sustainability. Similar to previous studies, results of the GRI index disclosure show a relatively low score, there is a possibility of a tendency to gain legitimacy from the GRI ‘brand’. Novelty : The research offers new insights into the factors that influence sustainability reporting in university. This study contributes to a better understanding of the determinants of university sustainability reporting.